Moral Grandstanding as a Narcissistic Intrinsic Satisfaction - Gamze Şen; Elif Manuoğlu (Psikiyatride Güncel Yaklaşımlar, 2022)
The aim of this study is to define the concept of moral grandstanding and discuss its antecedents, motivations behind it, and implications. Moral grandstanding is described as contributing to moral discourse to persuade others that one is morally respectable. Individuals who value their moral standing are more concerned about their own self than the topics that they claim to discuss. Therefore, it is likely that individuals who perform moral grandstanding may be high on the narcissistic personality trait. Although moral grandstanding can bring about reputation and fame to individuals, it can be associated with society contribution in some cases. While advertising their prosocial behavior, individuals’ true motivation may not be obvious. Thus, it is essential to understand their actual motivation for the behavior in question as well as their level of narcissism in order to understand whether the behavior is considered as an example of moral grandstanding. Pathological narcissism and the intrinsic-extrinsic motivation concept of self-determination theory were used to extend the current understanding of the moral grandstanding concept in the present study. Lastly, the real-life implications of moral grandstanding were discussed with reference to current issues like the pandemic.